Pengembangan Wisata Berbasis Masyarakat untuk Meningkatkan Perekonomian Masyarakat Desa Sekapuk Kecamatan Ujung Pangkah Kabupaten Gresik - Nasirudin Al Ahsani; Kharisma Fitrotul; Ana Fauziyah; Berliantin Nahdiya (Jurnal Al-Hikmah, 2021)
The water quality of the rivers in Gresik, specifically in Bengawan Solo river in Bungah-Ujung Pangkah area and the downstream of Brantas River in the Wringinanom-Driyorejo Region, is polluted as perceived from the total dissolved solids that reaches 5000 ppm. Meanwhile, the river water contaminated with microplastics in Bengawan Solo reaches 55.2/100 L and the downstream of Brantas River reaches 18.5/100 L3. The garbage does not only accumulate in rivers, but also on land. In Sekapuk Village, Ujung Pangkah Subdistrict, Gresik, there is a former limestone mine. Since the mining was completed, it ended up being a landfill from 2003 through 2017. The current study employs a qualitative research method. The data were collected from interviews, observation, and documentation. The objectives of this study are: 1) To determine the components of tourism and participatory planning in Setigi tourist attraction, 2) To determine the community development and empowerment in Setigi tourist attraction, and 3) to determine the supporting and inhibiting factors in managing Setigi tourist attraction. The results of this study are as follows: 1) Setigi tourist attraction's components include parking areas, toilets, prayer rooms, gazebos, photo spots, culinary areas, ATV cars, and others. The planning of this tourist attraction came from an idea of the village head to make the village into a tourist attraction. As a result, a regular meeting is held on the 1st of every month which is attended by members of BUMDES, PEMDES, other village institutions such as local community units (RT & RW) and other community members, 2) The community development is carried out by providing opportunities to establish stalls for women in family welfare program (PKK) groups and each local community unit (RT /RW) in Sekapuk Village, 3) The supporting factors are the ability and the willingness to establish Setigi tourist attraction. Meanwhile, the inhibiting factor is the limited funds in the tourist attraction development, but a joint saving program was planned by the village head.